Transcriptome analysis of sRNA responses to four different antibiotics in Pseudomonas aeruginosa PAO1. (December 2022) - Zhang, Wenlu; Li, Shasha; Deng, Bo; Wu, Pengfei; Shui, Yingbin; Zhang, Jiaming; Li, Zhongjie
Abstract: A large number of evidence showed that regulatory sRNAs could modulate antibiotic resistance and sensitivity. In this study, we used RNA-sequencing to profile sRNAs in wild type and antibiotic-resistant PAO1 selected by four antibiotics (polymyxin B, ciprofloxacin, doxycycline, and ceftriaxone). Totally, we found 113, 25, 91 and 12 differentially expressed sRNAs in polymyxin B-, ciprofloxacin-, doxycycline-, and ceftriaxone-resistant P. aeruginosa, respectively. To elucidate functions of differentially expressed sRNA, we predicated their target genes and obtained pathways enriched by their target genes. In addition, our results indicated that the downregulated sRNA spae884.1, spae3443.1, and spae5681.1 might involve in polymyxin B resistance by enhancing their target genes arnA, arnD, and arnT expression in PAO1, respectively. The upregulated sRNA spae3443.1 and spae649.2 might implicate in ciprofloxacin resistance by promoting their target gene pslK expression to increase biofilm formation in PAO1. The upregulated spae1558.1 might increase oprJ expression, as well as spae3959.1 and spae3706.1 might increase mexC expression to modulate doxycycline resistance in PAO1. The sRNA novel-N714 might involve in virulence in ceftriaxone-resistant PAO1 by activating its target gene PA1429 expression. Our study might provide bases of the underlying mechanism of sRNA in regulating antibiotic resistance of PAO1 against different antibiotics. Highlights: The spae884.1- arnA, spae3443.1- arnD, and spae5681.1- arnT might implicate in polymyxin B resistance in PAO1. The spae3443.1 and spae649.2 might upregulate their target gene pslK expression, resulting in ciprofloxacin resistance. The spae1558.1- oprJ, spae3959.1- mexC and spae3706.1- mexC might mediate doxycycline resistance in PAO1. The novel-N714 might regulate PA1249 expression, resulting in regulating virulence in ceftriaxone resistant PAO1.